Structural Dynamics, Marketing Pathways and Economic Performance of Nepalese Tea: Comparative Analysis of CTC and Orthodox Segments - Luitel, Gaurab; Panta, Hari Krishna; Dahal, Kishor Chandra; Timsina, Krishna Prasad; Bhusal, Tara Prasad (Nepalese Horticulture, 2025)
Tea is one of the horticultural cash crops which considerably contributes to export revenues and rural livelihoods in Nepal. It can be broadly divided into two categories: Crush, Tear & Curl (CTC) and Orthodox, each of which has its own production system and market structures. This study presents an in-depth analysis of the structural dynamics, marketing pathways, and economic performance of both segments. Using the primary data collected from 106 tea industries operating in Jhapa and Ilam, the study explores ownership patterns, green leaf sourcing strategies, processing capacity, market orientation, and economic performance. The results reveal that CTC industries are largely estate-based and chiefly cater the domestic demand, while Orthodox industries depend more on smallholder farmers and are export-oriented. Despite such structural and marketing divergences, both types of industries experience underutilized processing capacity. To examine economic performance and comparative advantage, the analysis estimated the cost of production (CoP) and Domestic Resource Cost (DRC) ratios for both tea types. The evidence reveals that Orthodox tea is costlier to produce, but offers a greater comparative advantage in foreign markets, as reflected by a lower DRC ratio. This situation suggests that while cost competitiveness remains a challenge, Orthodox tea has great potential in the global market from a resource efficiency point of view. Conversely, CTC tea is comparatively cheap and shows weak export competitiveness. To sum up, the research highlights the dual nature of Nepal’s tea economy, characterized by diverging pathways and market positioning, with implications for targeted policy support and strategic alignment based on comparative advantage.